To Economists about Jihad - R. I. Bekkin (Vestnik MGIMO-Universiteta, 2019)
The authors examine the role and place of Islam in international development and global governance in the context of pressing issues of inter-civilizational and inter-confessional interaction in the modern world, the challenges and threats that arise, including the problems of combating extremism and international terrorism. The authors focus on a comprehensive assessment and forecast of the development of the «Muslim segment» of the modern polycentric world, the conflict between the spatial expansion of traditional Islam and the neoliberal world order, the «Arab spring» phenomenon, mass management technologies from various political forces, the danger of regional destabilization and threats to global security and the interests of Russia.Author declares the absence of conflict of interests.